(untitled) (American Journal of Islam and Society, 2012)
It is a fact that the majority of Muslims are peace-loving citizens, who do not share or condone the motives, objectives, and activities of the violent minority. The former may not even hesitate to declare the latter as “not Muslims” due to their activities that are boldly antithetical to basic Islamic teachings and worldview. That would be, understandably, a religiopolitical perspective. But theologically ‒ it is not advisable, nor indeed, effectual to consider not as Muslim, anyone who truly believes in oneness of God, commits himself to following Prophet Muḥammad (ṢAAS) and actually performs the fundamentals of Islam, deviation and perversion notwithstanding. On the other hand, those extremist minority ‒ a fraction of the 7 percent of the global Muslim population considered to be “politically radicalized,” including sympathizers1 ‒ will surely consider their majority detractors not “true and sincere” Muslims. They certainly don’t believe the majority has the religious and moral authority over them. Unfortunately, from this perspective, the extremists remain, admittedly, part and parcel of Muslim fold ‒ regardless of whether or not the majority will accept it. And from this perspective of identity and actions that I will contend that not only are the extremists an inescapable nuisance, they remain a regrettable stigma that effects the larger Muslim majority ...